Warrior of the Altaii - Jordan, Robert, 1948-2007 (Tor fantasy., 2021)
The watering holes of the Plain are drying up, the fearsome fanghorn grow more numerous, and bad omens abound. Wulfgar, a leader of the Altaii people, must contend with twin queens, warlords, prophets and magic in hopes of protecting his people and securing their future. Elspeth, a visitor from another world, holds the answers, but first Wulfgar must learn to ask the right questions.